Cancer in IVF patients treated at age 40 years and older: long term follow-up. Issue 3 (March 2020) - Tsafrir, Avi; Lerner-Geva, Liat; Zaslavsky-Paltiel, Inna; Laufer, Neri; Simon, Alex; Einav, Sharon; Eldar-Geva, Talia; Holzer, Hananel; Gal, Michael; Hirsh-Yechezkel, Galit
Abstract: Research question: Current knowledge of cancer risk among women who undergo IVF is based mainly on studies of women treated in their thirties, frequently with short follow-up periods. Therefore, information about cancer risk among infertile menopausal women is limited. We aimed to evaluate the risk of cancer among IVF patients treated at age 40 years and older, followed up for an extended period. Design: Historical cohort study of all IVF patients treated at the age of 40 years or older at two university-affiliated IVF units in Jerusalem, Israel, between 1994 and 2002. Data were cross-linked with the Israel National Cancer Registry to 2016. Standardized incidence ratios (SIR) and 95% confidence intervals were computed by comparing the observed number of cancer cases with the expected cancer rate in the general Israeli population adjusted for age and year of birth. In addition, Kaplan–Meier analysis was conducted to account for the length of follow-up. Results: A total of 501 patients were included in the analysis, with mean follow-up of 16.7 ± 3.7 years (range 2–22 years). Mean age at first IVF cycle was 42.3 years (±2.1). Mean number of IVF cycles was 3.2 ± 2.6 (range 1–15). Thirty-six women (7.2%) developed invasive cancer, compared with 47.2 expected cases; SIR 0.76 (95% CI 0.53 to 1.06); 22 women were diagnosed with invasive breast cancer, compared with 19.84 expected; SIR 1.11 (95% CI 0.69 to 1.68). Conclusions: Older women undergoing IVF treatment were not significantly associated with an excess risk of cancer at long-term follow up. Further studies, however, are needed to confirm these findings.